A Brief Overview of the 33rd Annual STP Symposium on the Translational Pathology: Relevance of Toxicologic Pathology to Human Health. (January 2015) - Hoenerhoff, Mark J.; Silverman, Lee; Francke, Sabine
The 33rd Society of Toxicologic Pathology's Annual Symposium focused on translational science and the relevance of toxicologic pathology to human health. Toxicologic pathologists work in diverse settings studying changes elicited by pharmacological, chemical, and environmental agents and factors that modify these responses. Regardless of the work setting, society members are dedicated to the integration of toxicologic pathology into hazard identification, risk assessment, and risk communication regarding human and animal exposure to potentially toxic substances. Toxicologic pathologists routinely face not only questions regarding pathological changes related to compound exposure but also questions concerning what translational relevance those lesions and exposures have to a human population or organ system. This symposium provided a basis for the membership to understand the variety of roles the toxicologic pathologist plays in translational science, where our gaps in translational science are, and how we can move forward to better address the challenges in the field translational science in order to continue to positively impact human health.